2002
DOI: 10.1007/bf02557521
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors associated with long-term survival in patients with neuroendocrine tumors of the pancreas

Abstract: Definitive surgical resection of the primary tumor, absence of liver metastases, metachronous liver metastases, and aggressive treatment of the liver metastases were predictors of long-term survival in patients with neuroendocrine tumors of the pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
66
3
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(83 citation statements)
references
References 12 publications
12
66
3
2
Order By: Relevance
“…The median length of our follow-up, i.e. 42.5 months, is in agreement with the follow-up value reported in other studies (Burke et al 1997, Madeira et al 1998, Chu et al 2002, Hochwald et al 2002, Furlan et al 2004). This value is influenced by several elements, such as the inclusion of patients with recent diagnosis of GEP ET and the finding that most deaths occur at a short interval of time from diagnosis (median 18 months).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The median length of our follow-up, i.e. 42.5 months, is in agreement with the follow-up value reported in other studies (Burke et al 1997, Madeira et al 1998, Chu et al 2002, Hochwald et al 2002, Furlan et al 2004). This value is influenced by several elements, such as the inclusion of patients with recent diagnosis of GEP ET and the finding that most deaths occur at a short interval of time from diagnosis (median 18 months).…”
Section: Discussionsupporting
confidence: 92%
“…The survival rate observed in our series, for PETs, is in agreement with other studies (Rigaud et al 2001, Gullo et al 2003, in which a survival of 50-70% was reported. However, it is higher than the data reported by Modlin et al (2003) in a retrospective analysis of a cancer registry referring to the last three decades; and also data reported by Kent et al (1981), Chu et al (2002) and Lepage et al (2004) who reported a survival rate of 30-40%. This discrepancy is probably due not only to the different features of the populations studied, which included mostly patients with advanced disease, but also to the different design of the studies, generally retrospective (Modlin et al 2003, Lepage et al 2004, Chu et al 2002, Gullo et al 2003.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…These data suggest that in patients diagnosed with pancreatic NETs CgA evaluation might be useful to identify patients in which local and distant metastases should be looked for by an accurate clinical evaluation. This issue is important, since it has been previously demonstrated that in pancreatic NETs, the presence of metastases profoundly influences survival rate, which is significantly better in patients without metastases (Madeira et al 1998, Chu et al 2002, Gullo et al 2003, Panzuto et al 2005. Moreover, the 5-year survival rate was reported to be 60-100% for localized disease, 40% for regional disease, 29% for distant metastases, and 80% for all stages (Eriksson et al 1990, Modlin et al 2003.…”
Section: Discussionmentioning
confidence: 98%